Comparison of Cefoperazone + Sulbactam Versus Polymyxin B in the Management of Ventilator Associated Pneumonias Caused by Multi-Drug Resistant Acinetobacter - Fazal Rabbi; Ajab Khan; Syed Muhammad Muneeb Ali; Syed Mujahid Gilani; Taha Muhammad Usman Pasha; Aqsa Ahmad; Fazal Mustaan; Tawseef Ahmad (International Journal of Applied and Scientific Research, 2023)
The present study entails a comparative analysis of the efficacy of polymyxin B and cefoperazone with sulbactam in the treatment of pneumonias induced by multidrug-resistant Acinetobacter strains. In the experimental group, the gender distribution was exactly the same (males: 21; females: 15). More co-morbidities exist in Group-II than in Group-I. In groups I and II, the mean ICU stays were respectively 11.86 days plus 2.06 SD and 11.47 days plus 1.61 SD. Day 2 post-therapy saw group mean CPIS at 7.781.48 and group-II at 7.081.23, respectively. The clinical response was seen in group-I (n=11/36) and group-II (n=24/36) patients in accordance with our operational criteria. Similar mortality rates applied to both groups. In line with our hypothesis, 31% (n=9/29) of group I survivors and 65.6% (n=21/32) of group II survivors both showed effectiveness (p=0.007).